Obligation procedures of participatory democracy in the administrative centers of the districts of eastern Ukraine - Konotoptsev, Oleg (Theory and Practice of Public Administration, 2024)
The article highlights the results of assessing the degree of prevalence of participatory democracy tools in the territorial communities of eastern Ukraine, the obligation of which is determined by the legislation of Ukraine on local self-government. The article substantiates the choice of assessment objects and outlines the assessment methodology. During the assessment, the availability of procedures for holding general meetings of citizens at the place of residence, submission of local initiatives, organization of public hearings and appeals through electronic petitions was checked in territorial communities. The object of evaluation was the local self-government bodies of territorial communities, which became district centers after the territorial reform of 2020. 13 city councils in three Eastern Ukrainian regions of Ukraine – in Poltava, Sumy and Kharkiv regions – became such. During the evaluation, a high level of prevalence of mandatory tools of participatory democracy in the east of Ukraine was revealed. However, no tool has been implemented in all communities, which are the district centers of eastern Ukraine. But most of the tools are implemented in most communities. At the same time, electronic petitions and public hearings are the most fully implemented. In general, the assessment allows us to state that modern technologies of public management are quite widespread and are not something foreign and unfamiliar in territorial communities, which are the district centers of eastern Ukraine. Almost all mandatory instruments of participatory democracy have been implemented in almost all evaluated territorial communities. Therefore, there are sufficient grounds to assert that the territorial communities in the east of Ukraine (at least in the district centers) are ready for the expansion of the mandatory range of tools of participatory democracy, which will come in connection with the entry into force of the law on people’s power at the level of local self-government.